Pengembangan Customer Relationship Management (CRM) Sistem Umpan Balik Pelanggan (Customer Feedback System) pada Perusahaan XYZ - Ahmad Hayyi Muhyiddin; Agi Putra Kharisma; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The process of handling customer feedback at XYZ company is currently carried out by customer service via social media, feedback data is stored and managed in spreadsheets. Currently experiencing several problems, there is repeated delivery of feedback, there is no delivery of problem resolution to all customers, it is difficult to communicate further with customers because customer data is not detailed, so the feedback data is not up to date. In addition, it is necessary to prioritize customer feedback. As well as the process of handling feedback involving other divisions must go through customer service thereby slowing down performance. In solving these problems this research proposes to create a customer feedback system. In solving this problem, needs analysis, design, implementation, and testing are carried out by applying an object-oriented approach. The process of needs analysis is carried out by conducting requirements elicitation of business processes, to produce requirements specifications. The design process produces class, data, and interface designs that are used for the implementation process. The implementation process produces database implementation, program code implementation, and interface implementation. Then it was tested using the whitebox and blackbox methods to get it in line with the needs and designs that were made, and compatibility testing was also carried out to ensure the system could be accessed in all browsers.